Ekonomi Islam VS Ekonomi Kapitalis - Muhdar HM (Al-Ulum, 2010)
This paper describes some differences in the Islamic economic system and the capitalist economic system. The sources of Islamic economic system are clear, i.e., the Koran and the hadits. The foundation of Islamic economics is distinctive, unique and different with the capitalist economic system or socialist economic system. In a capitalist economic system, economic activities carried out solely to gain benefits and materials; hence, capitalist negates the interests of common people. There is also no guarantee of perfection in capitalist economic system; even it can lead disaster to the people.